What is the quality of life in patients with long COVID compared to a healthy control group? - Líška, Dávid; Liptaková, Erika; Babičová, Adriana; Batalik, Ladislav; Baňárová, Patrícia Shtin; Dobrodenková, Silvia (Frontiers in Public Health, 2022)
Introduction: Many patients have prolonged symptoms after COVID19 infection, which can affect patient quality of life (QOL). The aim of this study is to determine the quality of life in patients with long COVID, compared with healthy controls. Material and Methods: The study was a prospective cross-sectional study using an anonymous online survey. The SF-36 questionnaire was chosen for quality of life measurement. The survey was distributed through the Facebook social media platform targeting groups of patients with long COVID. The control group was made up of physiotherapy and physical education students. Results: There was a significant difference in physical function, with a mean score of 94.9 (± 9.4) among the students, compared to long COVID patients with a mean score of 66.2 (± 25.4) (p <0.001). A similar result was found in the physical role (p <0.001). The overall quality of life score for college students was 578.0 (± 111.9), and the overall score for patients with long COVID was 331.9 (± 126.9). Conclusions: Patients with long COVID had a lower quality of life compared to the healthy control group, and this was associated with the negative effect of long-COVID. Lower quality of life in patients with long COVID is an important therapeutic goal, which requires attention.